Comprehending the Marketing Strategies of Microfinance Institutions: Case of Selected Institutions within Multan District of Pakistan - Syedah Shan E. Ahmad (International Review of Management and Marketing, 2015)
The study focuses on finding whether micro finance institutions (MFIs) within Multan District of Pakistan use marketing approaches and strategies in credit delivery and savings mobilization. The objectives of the study are measuring the degree of marketing orientation among MFIs and probing the application of marketing in credit delivery and savings mobilization. The research aims to test the hypothesis that “whether or not Microfinance Institutions in Multan District are market oriented in delivery of credit and mobilizing the savings.” Primary data has been used as the main source of data for the study. The data was drawn from credit officers and management team (in some cases) of the microfinance institutions. Descriptive statistics have been used for analyzing the data by using excel sheets and SPSS software. The survey revealed that the certain MFIs are not market-oriented in services' delivery. One of the main finding is that marketing activities are poorly organized in MFIs. Moreover, little focus has been placed on marketing in corporate plans, and a very low budget has been allocated to promotional activities. In some cases no separate marketing promotional activities have been found. Unavailability of data is there and while conducting the survey lack of data transparency issue has been faced. The evidence in the paper suggests that MFIs should make marketing departments, develop the customer service packages in an easy approachable manner, and reinforce their marketing planning capabilities particularly in environmental awareness area. The paper is informative when planning for the establishment of proper marketing departments in MFIs.